What distinguishes ’good’ from ’bad’ industrial agglomerations? - Hassink, Robert (ERDKUNDE, 1997)
Modern theoretical concepts on regional economic development try to explain the economic success of a small group of regions. Some of these concepts are developed by economic geographers and sociologists who take the question ’why are some regions economically successful?’ as a starting-point, whereas others are developed by economists who focus on the question ’why do internationally successful industries tend to concen trate in a few nations or regions?’ These concepts share the attempt to explain the origin and development of innovation, stress the significance of industrial organisation for regional innovation processes and focus on success stories. The problem with most of these concepts, however, is that their central explanatory aspects cannot distinguish between ’good’ industrial agglomerations, such as the Third Italy and Silicon Valley, and ’bad’ ones, such as the Ruhr Area and Route 128 near Boston. The central aim of the article is to find out what distinguishes ’good’ from ’bad’ industrial agglomerations and at what point co-ordination of activities among the actors in an industry cluster turns from an advantage into a disadvantage. First, it will review modern theoretical concepts on regional economic development on this issue. Secondly, it will go deeper into work that stresses that the combination of technology and spatial clustering alone does not create mutually beneficial interdependencies, but that they are rather the result of organisational structures. This work distinguishes between regional network-based industrial systems as the basis for ’good’ agglomerations and independent firm-based industrial systems as the basis for ’bad’ ones.